ANALISIS PENGARUH JENIS AGEN CROSSLINKER TERHADAP KARAKTERISTIK PEREKAT KAYU BERBAHAN TEPUNG TAPIOKA DAN PVA - Bima Prasetya Pancasakti; Budhijanto Budhijanto; Vincent Vincent (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
This research aimed to analyze the characteristics of adhesive using the variation of crosslinking agents. The types of crosslinking agents were citric acid and oxalic acid which have the capability to create a bond with cassava starch-PVA adhesive. The synthesis process was conducted through gelatinization, hydrolysis, oxidation, and polymerization. The reaction was run using a three-neck flask and mercury stirrer at 70 °C and 1 atm. The characteristic of adhesive such as viscosity, dry and wet shear strength, solid content, durability, and surface morphology was analyzed based on the standard. The result depicted that the use of citric acid as crosslinking agent influenced the quality of the adhesive. Citric acid is able to enhance the viscosity and the strength of the dry and wet shear strength of the adhesive. The exact value of the dry and wet shear strength of the adhesive are 1,0173 and 0,7039 MPa. The addition of citric acid has a big impact on the thickness of the adhesive during the period. The morphology of the adhesive showed that the use of crosslinking agent had a big impact on the homogeneity level of the adhesive. Therefore, it can be concluded that citric acid with 2% of composition from cassava starch weight is a suitable crosslinking agent to enhance the quality of cassava starch-PVA adhesive.